Strategi Pengembangan Jalur Rempah di Wilayah Barat-Selatan Aceh sebagai Destinasi Wisata Halal: Analisis SWOT - Inayatillah; Junaidi; Fadhlur Rahman Armi (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
The Spice Route should serve as the main driver for developing tourism based on history, culture, and economy in Aceh, particularly in the West-South region. However, this area still faces limitations in infrastructure, a lack of digital promotion, and suboptimal management of its historical and cultural potential. This study aims to formulate strategies for developing the Spice Route in the West-South region of Aceh as a halal tourism destination, focusing on enhancing competitiveness, sustainability, and community empowerment. This article employs a descriptive qualitative approach, collecting data through document studies, non-participant observation, and semi-structured interviews with traditional leaders, policymakers, academics, and communities across five districts in the region. SWOT analysis was used to map the strengths, weaknesses, opportunities, and threats of the area’s development. The study recommends strengthening the branding of the Spice Route, revitalizing historical sites, improving infrastructure, and fostering Penta Helix collaboration to position the area as a center of history-based halal tourism.